Trust and reputation aware geographic routing method for wireless ad hoc networks. (2018) - Vamsi, P. Raghu; Kant, Krishna
We consider the problem of secure geographic routing (GR) in mobile wireless ad-hoc networks (WANETs). This paper presents a dependable and pragmatic trust and reputation aware geographic routing (TARA-GR) method for mobile WANETs to achieve self-adaptability, scalability, lightweight communication, and efficiency. It supports the GR decisions by the dynamic computation of consolidated trust value (CTV) of each node in the network by integrating direct and indirect trust values. With the calculated trust value, each source or forwarding node selects the trusted nodes to route the packets from the source to the destination. TARA-GR is integrated with a well known greedy perimetre stateless routing (GPSR) protocol. This integration is termed as TARA-GPSR. The simulation results have shown that TARA-GPSR significantly improved the network performance metrics, such as packet delivery fraction, throughput, and energy consumption.